A home-based prism adaptation training for neglect patients. (January 2020) - Fortis, Paola; Ronchi, Roberta; Velardo, Valeria; Calzolari, Elena; Banco, Elisabetta; Algeri, Lorella; Spada, Maria Simonetta; Vallar, Giuseppe
Abstract: Spatial neglect is a debilitating disorder frequently observed after damage to the right cerebral hemisphere. Previous investigations have revealed that prism adaptation (PA) therapy can lead to improvements in neglect-related symptoms. In the typical PA protocol patients repeatedly point toward a visual target while wearing prism goggles. A few years ago, a novel PA procedure, involving a variety of more "ecological" visuo-motor activities during adaptation, less repetitive than a sequence of pointings, was introduced by our research group, and shown to be able to improve neglect-related symptoms to the same extent as the standard pointing task. The ecological procedure was easy to administer and pleasant for the patients. In all previous studies, patients were treated by specialized personnel during hospitalization. In the current study, we investigated the effectiveness of the ecological PA method when performed in a home-based setting, with the help of caregivers and family members. Seven right-brain-damaged patients with chronic left spatial neglect underwent a two-week ecological PA treatment, extended, for two extra weeks, in 6 patients, who were available for this additional rehabilitation session. As a control treatment, patients performed the same activities while wearing neutral goggles, before the PA procedure. Two weeks of ecological PA training proved to be able to significantly improve performance in neuropsychological tests (BIT, Cancellation tasks), a neurological scale (NIH), and functional abilities (CBS), when compared to both the baseline and the neutral control treatment, with improvements being maintained over 6 months. The ecological home-based PA training is effective in alleviating signs of spatial neglect. Importantly, this training is affordable, pleasant, and feasible to be performed in the comfort of the patient's home. Easily extendable to larger patient populations and prolonged periods, this method has a real potential to benefit the quality of life of brain-damaged patients with left spatial neglect.